Ethanol extract of Cyclea barbata Miers induces follicle development through 17ß-estradiol level and LHR expression - Noviyanti Noviyanti; Yuyun Yueniwati; Bambang Rahardjo; Galuh W. Permatasari (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Docking analysis revealed that there are four novel compounds in barbata, including Zearalenone, Bis(2-ethylhexyl) phthalate, Benzanthrone, and Octytldecyl phthalate have stronger affinity -9.7; -9.6; -9,2; and -7.7 kcal/mol, respectively. The extract of barbata leaves increased follicle development (75%) by elevating estrogen levels and LHR expression at all doses.   ABSTRACT Objective: Infertility, often linked to anovulation from impaired follicular maturation, affects millions globally. Cyclea barbata Miers, a plant with estrogen-like properties, may enhance follicle development through hormonal modulation. This study evaluated the ethanol extract of C. barbata leaves for its ability to promote in vitro follicle development by increasing 17ß-estradiol levels and luteinizing hormone receptor (LHR) expression. Materials and Methods: Molecular docking analysis identified four novel compounds in C. barbata, Zearalenone, Bis(2-ethylhexyl) phthalate, Benzanthrone, and Octyl decyl phthalate, with binding affinities of -9.7, -9.6, -9.2, and -7.7 kcal/mol to estrogen receptor alpha (ESRa). Secondary follicles (2-3 mm) from goat ovaries were cultured in vitro using TCM-199 medium supplemented with 10% FBS, PMSG, hCG, and C. barbata extract at 25, 50, or 100 ppm for six days. Follicle maturation was assessed via microscopy for size, cumulus-oocyte complex formation, and polar body extrusion. 17ß-estradiol levels and LHR expression were analyzed using one-way ANOVA and LSD tests. Results: The 100 ppm dose achieved 75% follicle maturation, significantly higher than 25% at lower doses and controls. It increased 17ß-estradiol levels (36.83 ± 2.33 pg/mL, p < 0.000) and LHR expression (261.874 ± 54.606, p < 0.000), with dose-dependent effects confirmed by statistical analysis. Conclusion: C. barbata extract at 100 ppm enhances follicular maturation by elevating 17ß-estradiol and LHR expression, likely due to its estrogenic compounds. Further in vivo and clinical studies are needed to confirm its therapeutic potential for ovulatory disorders.